2021
DOI: 10.1177/2150132721993628
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence of Hepatitis B Virus Infection and Associated Factors Among Pregnant Women Attending Antenatal Care Services in Gedeo Zone, Southern Ethiopia

Abstract: Background: Hepatitis B virus infection is a major public health problem worldwide and is a major cause of morbidity and mortality. This study aimed to assess the prevalence of hepatitis B virus infection and associated factors among pregnant mothers in the Gedeo Zone, southern Ethiopia. Methods: An institution-based cross-sectional study was conducted among 479 pregnant women visiting governmental and private health facilities in the Gedeo zone from January to April 2019. We selected study participants using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 25 publications
4
8
4
Order By: Relevance
“…Having a history of abortion had 5.7 times the likelihood of infection with HBV in relation with those study participants who did not have the history. Like those in the current study, both variables are indicated as having significant association with HBV infection in a study held in Southern Ethiopia [47].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Having a history of abortion had 5.7 times the likelihood of infection with HBV in relation with those study participants who did not have the history. Like those in the current study, both variables are indicated as having significant association with HBV infection in a study held in Southern Ethiopia [47].…”
Section: Discussionsupporting
confidence: 59%
“…Having a history of abortion had 5.7 times the likelihood of infection with HBV in relation with those study participants who did not have the history. Like those in the current study, both variables are indicated as having significant association with HBV infection in a study held in Southern Ethiopia [ 47 ]. In agreement with the present study, the history of abortion was mentioned as one of the predictor variables for HBV infection in studies conducted in Ethiopia [ 30 , 48 ].…”
Section: Discussionmentioning
confidence: 72%
“…This prevalence rate is higher than different regions of Ethiopia which has been reported West Hararge public hospital 6.1% (1) Another study done in Amhara region and Addis Ababa shows that prevalence in Amhara region and 1 % (10) in Addis Ababa city was 36 % respectively. and lower than study from Southern Ethiopia, Gedeo Zone prevalence of 9.2% (11).…”
Section: Discussioncontrasting
confidence: 56%
“…The sample size for this study was determined using the single-population ratio formula. When the HBV proportion (9.2%) is taken from a previous study conducted in the Gedeo zone, 19 there is an error rate of 3%, a confidence interval (CI) of 95%, and a nonresponse rate of 5% was assumed.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that multiple sexual partner was associated with HIV positive. 17 – 20 Another study conducted in Oromia showed no factors significantly associated with HBV seropositivity. 21 …”
Section: Introductionmentioning
confidence: 99%